Serverless is More: From PaaS to Present Cloud Computing - van Eyk, Erwin; Toader, Lucian; Talluri, Sacheendra; Versluis, Laurens; Uta, Alexandru; Iosup, Alexandru (IEEE internet computing, 2018)
In the late-1950s, leasing time on an IBM 704 cost hundreds of dollars per minute. Today, cloud computing, that is, using IT as a service, on-demand and pay-per-use, is a widely used computing paradigm that offers large economies of scale. Born from a need to make platform as a service (PaaS) more accessible, fine-grained, and affordable, serverless computing has garnered interest from both industry and academia. This article aims to give an understanding of these early days of serverless computing: what it is, where it comes from, what is the current status of serverless technology, and what are its main obstacles and opportunities.